Copyright/design interface : past, present, and future - Derclaye, Estelle (Cambridge intellectual property and information law, 2018)
"Protecting designs is complex and diverse; it involves deciding whether to protect them by design law, copyright law, or by both laws. A single protection may be under- or overprotective but two or more can be overprotective if there are no rules regulating the overlap. Legal systems in Europe and abroad have struggled to find the most adequate solution to this problem. This book traces the history of the design/copyright interface of 15 countries, selected for their diversity in the way they dealt with the interface. It examines how these countries have coped with the problems engendered by the interface, the rules they applied to it over time and the reasons for legislative changes. This analysis reveals the most appropriate rules to regulate the interface at EU and global level and will appeal to academics, practising lawyers, judges, students and policymakers all over the world"--